An Asymmetrical Cyanine Dye Nanoparticles for Small Vessel Photoacoustic Imaging In Vivo. Issue 7 (13th June 2018) - Li, Yunzheng; Xiong, Jialiang; Shao, Zixing; Ai, Yongjian; Hua, Ruimao; Luo, Guoan; Liang, Qionglin
Abstract: A novel asymmetrical cyanine dye (TR) with NIR absorption at 970 nm was synthesized and applied in photoacoustic imaging (PAI) in vivo for the first time. The advantages of asymmetrical structure in PAI was demonstrated with DFT calculation and verified by related experiments. BSA was selected as the matrix to encapsulate TR‐BSA nanoparticles (TR‐NPs) which was investigated as a PAI agent. Exceptional performance of TR‐NPs was shown in Balb/c rats caudal vein model; the details could be clearly displayed and identified at a 0.1 mm scale. Abstract : Asymmetrical cyanine dye nanoparticles (TR‐NPs) were obtained through the combination of pyran and cyanine derivatives and subsequent encapsulation with BSA. TR‐NPs generate a strong photoacoustic imaging signal at 970 nm under various in vivo conditions, such as in the Balb/c rat caudal vein model. Both the high‐resolution observation of small vessels and multifunctional characteristics indicate the potential for small vessel imaging.